Genetic Polymorphisms in Fatty Acid Metabolism Modify the Association Between Dietary n3: n6 Intake and Risk of Ulcerative Colitis: A Prospective Cohort Study - Ananthakrishnan, Ashwin N; Khalili, Hamed; Song, Mingyang; Higuchi, Leslie M; Lochhead, Paul; Richter, James M; Chan, Andrew T (Inflammatory bowel diseases, 2017)
High intake of dietary n-3 polyunsaturated fatty acids (PUFA) is associated with a decreased risk of ulcerative colitis (UC) and Crohn's disease (CD). However, results have been heterogeneous suggesting that genetic variations in PUFA metabolism may modify this risk. We conducted a case-control study nested within 2 prospective cohorts, the Nurses' Health Study (NHS) and NHS II. Among women providing blood (n = 62,437) or buccal cells (n = 59,543) for genotyping, we confirmed new diagnoses of CD or UC. Dietary intake was assessed 4 years before diagnosis. Confirmed cases were matched 1:2 to controls. Subjects were genotyped for single nucleotide polymorphisms at CYP4F3, FADS1, and FADS2 loci. Conditional logistic regression models examined the interaction between genotype, n3:n6 PUFA intake and risk of CD and UC. Our study included 101 CD and 139 UC patients matched to 495 controls. On multivariable analysis, high intake of n3:n6 PUFA (above median) demonstrated a trend toward reduced risk of UC (Odds ratio [OR] 0.71, 95% confidence interval [CI], 0.47-1.09, P = 0.11). High n3:n6 PUFA intake was associated with a reduced risk of UC in individuals with the GG/AG genotype at a single nucleotide polymorphism in CYP4F3 (OR 0.57, 95% CI, 0.32-0.99) but not those with the AA genotype (OR 0.95, 95% CI, 0.47-1.93) (P-interaction = 0.049). No gene-diet interactions were noted for CD. The association between dietary n3:n6 PUFA intake and risk of UC may be modified variants at CYP4F3. Further gene-environment studies of the association between diet and IBD risk are warranted.